A new species and records of Gripopterygidae (Plecoptera) from Rio Grande do Sul State, Southern Brazil - Novaes, Marcos Carneiro; Bispo, Pitágoras Da Conceição [UNESP] (Magnolia Press, 2016)
Specimens of Gripopterygidae (Plecoptera) from Rio Grande do Sul State, southern Brazil were studied. A new species, Tupiperla sepeensis n. sp. is described. Tupiperla misionera Froehlich 2002 is a new record for Brazil and Gripopteryx reticulata Brauer 1866 and Tupiperla tessellata Brauer 1866 are new records for southern Brazil.
Keywords: Neotropical; Stoneflies; Streams